Resolution of Internal Carotid Arterial Thrombus by the Thrombolytic Action of Dabigatran: A first case report. Issue 14 (April 2016) - Akiyama, Hisanao; Hoshino, Masashi; Shimizu, Takahiro; Hasegawa, Yasuhiro
Abstract : Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs) have been reported to cause resolution of intracardiac thrombus, but there have been no reported cases of internal carotid arterial thrombus resolution. We report a case of a 76-year-old man in whom an internal carotid arterial thrombus resolved after administration of the NOAC dabigatran at a dose of 110 mg twice daily. This is the first reported case of carotid arterial thrombus resolution after oral intake of NOAC (direct thrombin and factor Xa inhibitors), to the best of our knowledge. We conclude that this case had major clinical significance because it might represent one of the multiple effects of NOACs.